2021
DOI: 10.1186/s12879-021-06863-5
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine acceptance, hesitancy, and determinants among physicians in a university-based teaching hospital in Thailand

Abstract: Background The COVID-19 vaccines provide renewed hope in the fight against the recent pandemic. To ensure widespread vaccination, it is crucial to analyze vaccine willingness and its determinants among physicians, key health care influencers. This study aimed to assess acceptance rate and identify factors associated with vaccine hesitancy among Thai physicians. Methods A cross-sectional online-based questionnaire was distributed to all physicians a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 27 publications
8
55
1
Order By: Relevance
“…A study carried out in Colombia found that 90.7% of medical personnel are willing to be vaccinated with an 80.0% effective vaccine [ 13 ]. This figure is similar to that reported by studies in Thailand, where a 95.6% vaccination intention was reported by medical personnel [ 14 ]. However, a study conducted on Chinese factory workers found that the rate of vaccine acceptance in this population ranged from 66.6% to 80.6% [ 15 ].…”
Section: Introductionsupporting
confidence: 91%
“…A study carried out in Colombia found that 90.7% of medical personnel are willing to be vaccinated with an 80.0% effective vaccine [ 13 ]. This figure is similar to that reported by studies in Thailand, where a 95.6% vaccination intention was reported by medical personnel [ 14 ]. However, a study conducted on Chinese factory workers found that the rate of vaccine acceptance in this population ranged from 66.6% to 80.6% [ 15 ].…”
Section: Introductionsupporting
confidence: 91%
“…In this study, the pooled prevalence (51.64%) is in line with systematic reviews conducted in Africa (48.93%), Kuwait (53.1%), and Somalia (59.4%) [ 8 , 35 , 36 ]. However, the finding is lower than other systematic reviews conducted at the global level (71.5%), India (86.3%), Thailand (95.7%), and Bangladesh (65.5%) [ 37 40 ]. Likewise, the pooled prevalence is higher than studies conducted in Nigeria (40%) and Tunisia (35%) [ 41 , 42 ].…”
Section: Discussioncontrasting
confidence: 61%
“…In these countries, specific vaccines promoted by national authorities were less likely to be chosen by those who supported political parties opposing the ruling government. As our data from Thailand also show, some vaccines were partly rejected as they were viewed as less efficacious against infection prevention and serious disease, consistent with findings reported from physicians in that country [ 21 ]. In both our studies, males and older respondents were more likely to express willingness to vaccinate, in line with data collected elsewhere [ 46 , 59 ].…”
Section: Discussionsupporting
confidence: 88%
“…Government and royal support for a small bioscience company, with no history of vaccine manufacturing, contributed towards vaccine scepticism, a delayed rollout, and raised questions about the political stance of AstraZeneca, produced under license in Thailand at the time [ 18 , 19 , 20 ]. At the same time, there were media reports of widespread demands for mRNA vaccines, perceived by many Thais as more effective in preventing disease [ 18 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%